Comment on “Voltage-Mode All-Pass Filters Including Minimum Component Count Circuits” - Abhirup Lahiri (Active and Passive Electronic Components)
This comment is related to the recently published article “Active and Passive Electronic Components” by S. Maheshwari (2007), which presents single current differencing buffered amplifier (CDBA) and current-controlled current differencing buffered amplifier- (CC-CDBA-) based first-order voltage-mode (VM) all-pass filtering (APF) sections. The paper is reviewed, and additional first-order APF realizations have been proposed.